Penggunaan metode ekstraksi maserasi dan partisi pada tumbuhan cocor bebek (kalanchoe pinnata) dengan kepolaran berbeda - Tri Reksa Saputra; Agustinus Ngatin; Yunus Tonapa Sarungu (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2018)
Has conducted research of the preparation Cocor Bebek plants as raw materials for corrosion test by using two methods of extraction are maceration and partition. Maceration process is done by using methanol, which will then be concentrated by using a rotary evaporator to produce concentrated methanol extract. The next stage is the process of partitioning using a solvent n-hexane and ethyl acetate, and of the steps that have been made, from the fresh leaves Cocor Bebek generated as much as 10.3 kg of concentrated methanol extract as much as 65.7442 g, n-hexane extract as much as 36.1452 g, and the ethyl acetate extract as much as 15.2711 g.